Desa Peduli Pendidikan melalui pendampingan penulisan Karya Ilmiah (laporan PTK) - Eko Purnomo; Kodrat Hi Karim (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The publication of scientific papers is an essential element in promoting educators. The problem is that the average teacher at SD Negeri 45 has not written and published independently. Some teachers are not proficient in operating computers, especially Microsoft Office Word. Even though writing scientific papers requires these skills to facilitate the work of teachers during writing. In this service, several points are trained, namely optimizing the use of Microsoft Office Word, the rules of writing scientific reports and publications, and techniques for implementing CAR. This activity was carried out on September 18, 2021. The partners of this service were all teachers at the 45 Ternate State Elementary School. The method used is demonstration, lecture, and question and answer. The results of community service activities show that teachers at SD Negeri 45 Ternate City can write CAR scientific reports even though only three people have the best writing skills. At the evaluation stage, several corrections were found, such as spelling errors, data analysis techniques, and the use of references. The obstacle in this research is the limitations of laptops and computers. It takes a long time because there are three available laptop facilities during practice, so the teacher is divided into 3 study groups. However, overall, this service can provide understanding and motivation to teachers at SD Negeri 45 Ternate City to write scientific papers